Bioactive Cembranoid Composition in the Soft Coral of Sarcophyton glaccum on The Response to Changing pH - Neviaty Putri Zamani; Dedi Soedharma; Ekowati Chasanah; Hedi Indra Januar (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2017)
Soft coral is predicted to outcompete with hard coral in future ocean acidification scenarios. Beside the biological resilience shown in acidic conditions, soft corals ability to maintain or compete for space is shown to relate with their ability to produce cytotoxic cembranoid-type compounds. The aim of this study was to investigate composition of cytotoxic cembranoid compounds of Sarcophyton glaccum soft coral exposed to current and predicted future ocean acidification scenarios. Sarcophyton glaccum colonies were acclimated along a pH gradient to simulate predicted increases in ocean acidification: natural/current (pH 8,2), slight increase in acidification (pH 8.0 year-1 2060), and moderate increase in acidification (pH 7,8 year-1 2100). Cembranoid composition was determined by quantitative Nuclear Magnetic Resonance spectroscopy while cytotoxic activity was determined against tumor cell lines. Results of the study showed cytotoxicity and sarcophytoxide (the most active cembranoid compound in observed Sarcophyton glaccum) were both found to be higher at pH 8,0. However, a further increase of acidification resulted on a reduction of both the cytotoxicity and sarcophytoxide production. This suggests that acidification pressures affect directly the defense system metabolism of Sarcophyton glaccum and that while they may be resilient to small decreases in pH, their ability to compete for space may be hampered by more pronounced changes. Keywords: Cembranoids; Cytotoxic; Sarcophyton glaccum; Seawater Acidification; Soft Coral.